Transport modelling in the context of the ‘predict and provide’ paradigm - Næss, Petter; Andersen, Jeppe; Nicolaisen, Morten Skou; Strand, Arvid (European Journal of Transport and Infrastructure Research, 2014)
The central concern of this paper is why the traffic-increasing effect of road capacity expansion (induced traffic) is still frequently ignored when preparing decision-support material for proposed infrastructure investments. Earlier research has pointed at ignorance or technical difficulties as likely reasons. This paper offers an additional explanation. Based on an investigation of the opinions of transport modellers, consultants, transport planners and politicians concerning the usefulness, shortcomings and application of forecasting models in transport planning, this paper suggests that transport model forecasts are used in project evaluations primarily to throw light on where and when to build a proposed road infrastructure, not for assessing whether to build it. Since induced traffic is usually not differing so much between the different ‘build’-alternatives, the errors caused by omitting induced traffic in the models are accepted. This way of framing the decision problem is often associated with what has been termed the ‘predict and provide’ paradigm.